Empowering the Innovative Entrepreneurship Culture: Understanding the Key Factors and Government Supports from the Perspective of Senior Omani SMEs - Alhattali, Khalid Suraid Salim; Omar, Rosmini; Alrumaidhi , Sulaiyam Aziz; Ramely, Aslinda (Business Management and Strategy, 2024)
With the Sultanate of Oman promoting innovation-driven entrepreneurship and enacting legislation to facilitate the rapid expansion of creative start-ups, this study found a need to explore both types of innovative entrepreneurs and entrepreneurial innovation. Following that, the purpose of this qualitative study is to explore the key factors involved in becoming an innovative entrepreneur from the perspective of fifteen senior Omani SMEs and to understand the support received by them in promoting entrepreneurial innovation. They were selected and interviewed using the purposive sampling technique. The study's findings revealed five key factors involved in becoming an innovative entrepreneur, including (i) technology adoption; (ii) knowledge of the business environment and rivals as well as resilient; (iii) positive attitudes; (iv) financial management; and (v) focusing on customers. However, only some of them received government support, such as lectures, workshops, and financial assistance or loans. This paper believes that identifying these key factors allows other SMEs to imitate similar factors, thus embarking on an innovative culture in their businesses. The understanding of the support given by the government allows this study to track the efforts made by the government in their effort to encourage innovation-driven entrepreneurship.